Co-fertilization of Sulfur and Struvite-Phosphorus in a Slow-Release Fertilizer Improves Soybean Cultivation - Valle, Stella F.; Giroto, Amanda S.; Guimarães, Gelton G. F.; Nagel, Kerstin A.; Galinski, Anna; Cohnen, Jens; Jablonowski, Nicolai D.; Ribeiro, Caue (Frontiers in Plant Science, 2022)
In face of the alarming world population growth predictions and its threat to food security, the development of sustainable fertilizer alternatives is urgent. Moreover, fertilizer performance should be assessed not only in terms of yield but also root system development, as it impacts soil fertility and crop productivity. Fertilizers containing a polysulfide matrix (PS) with dispersed struvite (St) were studied for S and P nutrition due to their controlled-release behavior. Soybean cultivation in a closed system with St/PS composites provided superior biomass compared to a reference of triple superphosphate (TSP) with ammonium sulfate (AS), with up to 3 and 10 times higher mass of shoots and roots, respectively. Root system architectural changes may explain these results, with higher proliferation of second order lateral roots in response to struvite ongoing P delivery. Plants reached between 1942 and 4291 cm of total root length under St/PS composites and only 982 cm with TSP/AS. While phosphorus uptake efficiency was similar in all fertilized treatments (11-14%), St/PS achieved a 22% sulfur uptake efficiency against only 8% from TSP/AS. Overall, the composites showed great potential as efficient slow-release fertilizers for enhanced soybean productivity.